Women and elective office past, present, and future - Thomas, Sue 1957-; Wilcox, Clyde 1953- (Oxford University Press, 2014)
A comprehensive look at where women candidates and officeholders stand at this moment in time, what brought them to this point, and what their prospects are in the 21st century.